1996
DOI: 10.2307/3870473
|View full text |Cite
|
Sign up to set email alerts
|

UV-B, UV-A, and Blue Light Signal Transduction Pathways Interact Synergistically to Regulate Chalcone Synthase Gene Expression in Arabidopsis

Abstract: UV and blue light stimulate transcription of key flavonoid biosynthesis genes in a range of higher plants. Here, we provide evidence that several distinct "inductive" and "synergistic" UV/blue phototransduction pathways regulate chalcone synthase (CHS) gene transcription and transcript accumulation in Arabidopsis leaf tissue. Experiments with the long-hypocotyl hy4-2.23N mutant showed that separate inductive pathways mediate responses to UV-B and UV-A/blue light. Only the UV-A/blue light induction of CHS expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
88
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(96 citation statements)
references
References 0 publications
8
88
0
Order By: Relevance
“…Soitamo et al, (2008) reported that light at low temperature induces the expression of genes involved in the synthesis of phenylpropanoids, carotenoids, and terpenoids. In Arabidopsis, the biosyntheses of light-dependent flavonoids and phenylpropanoids have been attributed to the upregulation of related genes at the transcript level and associated with an increase in primary metabolite production (Fuglevand et al, 1996;Hemm et al, 2004). The upregulation of GbMVD under light conditions possibly increases carbon partitioning towards terpenoid metabolism, resulting in increased TTL content in G. biloba.…”
Section: Discussionmentioning
confidence: 98%
“…Soitamo et al, (2008) reported that light at low temperature induces the expression of genes involved in the synthesis of phenylpropanoids, carotenoids, and terpenoids. In Arabidopsis, the biosyntheses of light-dependent flavonoids and phenylpropanoids have been attributed to the upregulation of related genes at the transcript level and associated with an increase in primary metabolite production (Fuglevand et al, 1996;Hemm et al, 2004). The upregulation of GbMVD under light conditions possibly increases carbon partitioning towards terpenoid metabolism, resulting in increased TTL content in G. biloba.…”
Section: Discussionmentioning
confidence: 98%
“…In a great variety of plant species the de-novo synthesis of CHS can be enhanced by irradiation with light, especially UV light . Dierent light qualities often interact synergistically (Fluglevand et al 1996) in stimulating¯avonoid accumulation. In other cases the transduction pathways are independent (Batschauer et al 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1998, Moriguchi et a/. 1999) and a variety of environmental stimuli such as light(Fuglevand et a/. 1996, Glassgen et a/.…”
mentioning
confidence: 99%